Aircraft maintenance manpower shift planning with multiple aircraft maintenance licenced. (April 2019) - Permatasari, C I; Yuniaristanto,; Sutopo, W; Hisjam, M
Abstract: Effective manpower shift planning can reduce labor costs, improve service, and customer satisfaction. This can be an (Maintenance, Repair, and Overhaul) MRO industry effort to minimize cost. MRO industry must be able to ensure that labor is always available when there is an incoming service and shift planning. This research will develop a mathematical model that can be used to determine the optimal allocation and shift planning of the manpower. Optimal allocation and shift planning of the manpower will affect the total cost, so a minimum total cost is obtained. For this research the method chosen was Integer Linear Programming (ILP). With the help of software ILOG CPLEX 12.8.0.0. From the results, it was found that there was 30% decrease in cost.